Validation of tiger beetles as distinct family (Coleoptera: Cicindelidae), review and reclassification of tribal relationships. (23rd June 2020) - Duran, Daniel P.; Gough, Harlan M.
Abstract: The higher‐level taxonomy of tiger beetles is re‐evaluated in light of recent publications based on large taxon sets and a large number of genetic loci. These studies have demonstrated that tiger beetles are a distinct family, Cicindelidae Latreille, sister to the Carabidae Latreille (ground beetles) or Trachypachidae Thomson (false ground beetles) + Carabidae. Recent phylogenies have also recovered consistent patterns in higher‐level relationships within the tiger beetles that challenge the traditional taxonomic framework, most of which is more than a century old. These phylogenetic results are reviewed along with concordant morphological characters to create an updated higher‐level classification. The subfamily Collyrinae Csiki is not supported by any modern data. We recognize six tribes, Manticorini Laporte (new sense), Megacephalini Laporte (new sense), Collyridini Brullé, Ctenostomatini Laporte, Cicindelini Latreille and the reinstated Oxycheilini Chaudoir (with emended spelling). Abstract : Tiger beetles are one of the most well‐studied groups of insects, yet the taxonomy of the group remains outdated, and few revisions have incorporated the results of modern molecular systematics. The higher‐level taxonomy of tiger beetles is re‐evaluated in light of recent publications based on large taxon sets and a large number of genetic loci. We recognize six tribes, eliminating Amblycheilini, Omini and Platychilini under Manticorini, restricting Megacephalini to include only the taxa previously included in Megacephalina and reinstate Chaudoir's Oxycheilini.